ANALYSIS OF FINANCIAL BONDS, SOCIAL BONDS, STRUCTURAL BONDS, AND EFFECT ON CUSTOMER LOYALTY IN WEST HEALTH CENTER IN SURABAYA - Kartika, Chandra (British Journal of Marketing Studies, 2014)
This study aims to provide most of the answers to the problems of the customer relationship services provided to the health center, due to the size of the outside observation and the more down's values on the dimensions of Relationship marketing in West Surabaya-district health centers, a growing number of complaints arising from the customer about the connection service provided to the patient, thus affecting the level of customer loyalty, and therefore researchers will examine issues very krausal to improve the level of health center services relationships and to increase the value of customer loyalty, especially patients in health centers of West Surabaya and will examine the effect of of Relationship Marketing to influence customer loyalty PHC. The sample in this study of 100 respondents were drawn from patients who never seek treatment at each Puskesman Surabaya West of seven (7) where the research that has been determined in the study in West Surabaya. This study uses quantitative and qualitative analysis through methods approaches and multiple linear regression analysis using software SPSS for Windows 20.0, from the findings expected to be found positive results and can reflect the broader quality and certainty in order to help improve the level of Relationship loyalty marketing in the health center of West Surabaya